BUSINESS SUSTAINABILITY SECRETS: IMPLEMENTING AN EFFECTIVE FINANCIAL STRATEGY - Loso Judijanto; Sri Dewi Yusuf; Rosdiana Imroati Kurnia Tanjung; Mohammad Taqiuddin Mohamad (Adisam Publisher, 2024)
In an ever-changing and uncertain business world, business sustainability is a top priority for stakeholders. One of the main keys to achieving this sustainability is through the implementation of an effective financial strategy. This article explains the financial strategy of business sustainability and the obstacles it faces. The research methods used in this study are literature that corresponds to the context of the research. The findings from this study are that the sustainability of a successful business depends heavily on the implementation of an effective financial strategy, which takes into account challenges such as market uncertainty, resource constraints, and internal conflicts. Efficiency in financial management can be enhanced through the use of advanced technology and human resource capacity development. With a comprehensive and adaptive approach, companies can cope with market fluctuations and long-term growth and stability.